Usos del adverbio donde en el habla lojana - Castillo Cuenca, Karol Vanessa (2022)
The adverb where has a wide semantic field, so its use has some variants, among them, the presence and absence of antecedents, as well as prepositions that give it new meanings. Therefore, the aim of this research is to analyse the uses of the adverb donde in Lojano speech. For this purpose, a recorded corpus of 27 interviews with men and women from five cantons in the province of Loja was analysed, taking into account some social variables such as: sector of residence, gender and generation. Finally, the results extracted from the study show that donde retains its locative value and greater use when it presents antecedents that allude to a place. In the same way, onde alternates with donde, preserving a locative situation especially in the canton of Catamayo.